Co-existence of metastatic uterine sarcoma and orbital sarcoidosis: A case report and literature review - Shalini, Surabhi; Mellington, Faye (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2022)
A 77-year old lady with previously treated endometrial sarcoma presented with progressive left upper lid mechanical ptosis secondary to superior orbital mass. An orbital biopsy confirmed the diagnosis of orbital sarcoidosis. Further systemic work up revealed suspicious pulmonary nodules which were found to be endometrial sarcoma metastases rather than systemic sarcoidosis on image guided biopsy. She was treated with 20 months of chemotherapy for metastatic sarcoma. The ptosis completely resolved, however, pulmonary metastases progressed despite chemotherapy. The co- existence of malignancy with sarcoidosis should be considered in all cases of new onset sarcoidosis. Biopsy of suspicious lesions, close observation and multidisciplinary team management is advocated for these patients.